EVALUASI KESESUAIAN LAHAN TANAMAN KAKAO (Theobroma cacaoL.) BERDASARKAN ANALISIS DATA IKLIM MENGGUNAKAN APLIKASI SISTEM INFORMASI GEOGRAFI - Safuan, La Ode; Kandari, Aminuddin Mane; Natsir, Muhammad (Jurnal Agroteknos, 2013)
The aims of the study were to determine the type of climate and the distribution and wide of   each class of climate suitability for cocoa crop in the district of Buton. This study was conducted in March   to August 2012 by using spline interpolation through the application of Geographic Information Systems (GIS) and ArcGIS 9.3 software and overlay method to get climatic units in the research are. The research found that climate type in the research area was climate type C (rather wet), subdistricts Batauga, Lasalimu, South Lasalimu, Siotapina and part region of including sub district Wolowa; and climate type D (medium) in the region of sub ditricts Kapontori, Wabula, Lapandewa and Sampolawa and part region sub district Wolowa, Lasalimu and Pasarwajo. Based on the results of evaluation of the suitability of the actual climate in the study area for the development of cocoa plants, there were nine (9 ) units of climatic suitability classes, namely S1, S2t, S2t, w1, S2w1, S3w1, S3w1, 3, S3w3, N1w3, and N2w1 with the area sizes of 91,16 ha or 0,08 %, 14.191,47 ha or 12,54 %, 10.726,04 ha or 9,47%, 2.245,34 ha or 1.98 %, 19.324,25 ha or 17,07 %, 17,80 ha or 0,02 %, 7.908,03 ha or 6,99 %, 29.017,40 ha or 25,63 % and 29.692,10 ha or 26,23 %. On the other hand, the potential climatic suitability classes were seven (7) units, namely S1, S2t, S2w1, S3w3, N1w1,3, N1w1 and N1w3 with each area size of 2.336,50 ha or 2,06%, 24.917,51 ha or 22,01%, 17,80 ha or 0,02%, 27.232,28 ha or 24,05%, 4.068,60 ha or 3,59%, 25.623,49 ha or 22,63% and 29.017,40 ha or 25,63% respectively, of the total evaluated area, with the limiting factors  of  temperature, climate, the  number of  dry  months  and  moisture.  This research showed that there are areas that can be developed for cocoa crop in the study area based on climate suitability. Keywords: climate, cocoa, land suitability